2017
DOI: 10.1159/000481944
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Trends in Methicillin-Resistant Staphylococcus aureus Isolated in Kuwait Hospitals: 2011-2015

Abstract: Objective: The aim of this study was to determine antibiotic resistance trends and carriage of staphylococcal cassette chromosome mec (SCCmec) genetic elements in methicillin-resistant Staphylococcus aureus (MRSA) isolated in Kuwait hospitals to ascertain whether they were healthcare associated (HA-MRSA) or community associated (CA-MRSA). Materials and Methods: In total, 6,922 MRSA isolates obtained from different clinical samples were tested for resistance toantibiotics, urease production, and carriage of SCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
4
29
0
Order By: Relevance
“…Significantly, the prevalence of high-level mupirocin resistance decreased from 3.7% in 2016 to 2.4% in 2017. This is consistent with previous report of low prevalence of high-level mupirocin resistance in Kuwait hospitals in recent years [9]. This is reassuring because it indicates that mupirocin can still be used successfully to control MRSA infections.…”
Section: Discussionsupporting
confidence: 92%
“…Significantly, the prevalence of high-level mupirocin resistance decreased from 3.7% in 2016 to 2.4% in 2017. This is consistent with previous report of low prevalence of high-level mupirocin resistance in Kuwait hospitals in recent years [9]. This is reassuring because it indicates that mupirocin can still be used successfully to control MRSA infections.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, 2 out of 100 people are carriers of CA-MRSA (CDC, 2016 ); which is particularly worrying as CA-MRSA can more easily spread than HA-MRSA. It has been suggested that there may be a more mobile genetic element in CA-MRSA as compared to HA-MRSA (Udo and Boswihi, 2017 ; Boswihi and Udo, 2018 ). According to CDC, a CA-MRSA is categorized as such if infection is evident on admission or a MRSA culture was obtained within 48 h of admission, with no history of admissions or medical treatment requiring invasive procedures (Gorwitz et al, 2006 ).…”
Section: Epidemiology Of Mrsamentioning
confidence: 99%
“…It wasthen followed by tetracycline having a mean susceptibility of 95%; while penicillin G was ineffective with 94 cases having 0% susceptibility [18]. Whereas the prevalence of resistance to most antibiotics showed annual variations, those resistant to chloramphenicol and rifampicin increased from 2.6 and 0.1% to 9.6 and 1.6%, respectively, and high-level mupirocin resistance declined from 9.3% in 2011 to 3.6% in 2015 [19].…”
Section: Discussionmentioning
confidence: 99%